2013
DOI: 10.1159/000345601
|View full text |Cite
|
Sign up to set email alerts
|

Is the Standardized Uptake Value of FDG-PET/CT Predictive of Pathological Complete Response in Locally Advanced Rectal Cancer Treated with Capecitabine-Based Neoadjuvant Chemoradiation?

Abstract: Objectives: Our aim was to assess FDG-PET/CT as a surrogate biomarker of the pathological complete response in locally advanced rectal cancer treated with neoadjuvant chemoradiation. Methods: T3–4 and/or N+ rectal cancer patients were treated prospectively with capecitabine-based chemoradiation and total mesorectal excision 7–8 weeks later. FDG-PET/CT uptake was obtained at baseline, after 2 weeks, and 6 weeks following treatment completion, calculating the maximum standardized uptake value (SUV) and percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…A higher decrease in SUV was found predictive for pCR by seven authors [26,41,44,45,[50][51][52]. Optimal cutoff values for RI SUVmax post vary from 45.9% to 76%.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A higher decrease in SUV was found predictive for pCR by seven authors [26,41,44,45,[50][51][52]. Optimal cutoff values for RI SUVmax post vary from 45.9% to 76%.…”
Section: Resultsmentioning
confidence: 95%
“…SUVmax post tends to be lower in patients without residual tumor cells than in patients with suboptimal treatment response. Optimal cutoff points to discriminate patients who achieve pCR from those who do not, vary between 3.35 and 5.4 [41][42][43][44][45]48,50].…”
Section: Resultsmentioning
confidence: 99%
“…Improved accuracy was reported by Bampo et al . where a posttreatment SUVmax of ≤ 5.4 showed a sensitivity of 80% and specificity of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…However, several small studies have indicated a correlation between metabolic and pathologic response and demonstrated a superior NPV (up to 95.5%) of FDG PET-CT for CPR compared with MRI in LARC restaging. [33][34][35] Furthermore, a recent systematic review combining results of over 1500 patients found a high pooled accuracy for early PET restaging post-CRT for LARC.…”
Section: Oesophageal Carcinomamentioning
confidence: 99%